A Simplified Nonlinear Method for a Laterally Loaded Pile in Sloping Ground - Pingbao Yin; Wei He; Zhaohui Joey Yang (Advances in Civil Engineering)
A simplified nonlinear method was proposed to evaluate lateral behavior of a pile located in or nearby a slope, based on the traditional p-y method. This method was validated with field test results of a steel pipe pile in clay and model tests of piles in sand slopes. The comparison indicated that the calculated horizontal displacement and bending moment of piles agree well with experimental results. Then, parametric studies were performed, and it shows that horizontal displacement, rotation, bending moment, and shear force increase along with increasing slope angles; the depth of maximum moment locates at about 1.6 D below ground surface for horizontal ground, while this value turns to be about 3.6 D and 5.6 D for sloping ground of 30° and 60°, respectively. The study clearly shows that slope angle has a significant effect on the deflection and lateral capacity of piles.